Percepción de los adolescentes de clase socioeconómica media, baja, urbana y baja marginal de Lima respecto a las prácticas de crianza de sus madres res sus - Majluf, Alegría (1993)
Based on a previous research by Majlufin 1989, an exploratory study was carried out to prove the degree of similarity between the mothers' rearing practices and the adolescents' perception of these practices. Block's Child-Rearing Practices Report was administered to 160 adolescents from middle, low and marginal SES (40 in each SES) coming from public and private schools of Lima. Results show differences between adolescents from middle and low SES and those coming from marginal areas of Lima conceming the democratic style. No differences were observed among the three groups with regard to their mothers affection. Significant differences were observed among the three groups conceming the authoritarian style. Adolescents from low SES see their mothers as less authoritarian than adolescents of middle SES and those from marginal areas. Results are discussed.